The impact of genetic counseling on women's grief and coping following termination of pregnancy for fetal anomaly. Issue 2 (26th October 2020) - Smith, Cayleen; Hashmi, Syed S.; Czerwinski, Jennifer; Wagner, Victoria F.; Promecene, Pamela; Milentijevic, Irena; Ramdaney, Aarti
Abstract: Pregnancy termination for fetal anomaly (TFA) is a unique experience that can cause women to develop long‐term complicated grief. Although a woman's experience with her healthcare providers has been previously identified as an important factor in coping, studies have shown that many women report their health care as lacking to some extent. Given the overlap in women's needs and the practice scope of a genetic counselor (GC), this study aimed to examine how genetic counseling may impact coping and explore women's expectations of GCs pre‐ and post‐TFA. An online survey, which included the brief COPE and the short version of the Perinatal Grief Scale, was distributed among private online support groups. Appropriate statistical analysis tools, such as the Wilcoxon rank‐sum and t test, were utilized for quantitative analysis of the 124 responses, and inductive content analysis was utilized for qualitative analysis. Of those who underwent TFA within the last two years, women who saw a GC utilized active coping, planning, and positive reframing significantly more than women who did not see a GC ( p  = 0.001, p  = 0.031, p  = 0.027, respectively). GCs were perceived to have a positive impact on coping when providing information, objective care, emotional support, support resources, and follow‐up care; these practices encouraged confidence in their personal decision‐making and gave women hope for the future. This study not only identified key counseling roles for GCs prior to a TFA, but also demonstrated that genetic counseling prior to TFA may be beneficial to coping. Further studies are warranted to explore the needs of a more diverse population and to identify appropriate genetic counseling training methods to support women pursuing TFA.